Thiocarbonyl Compounds in [4+2] Cycloadditions: Preparative Aspects - Breu, Josef; Höcht, Peter; Rohr, Uwe; Schatz, Jürgen; Sauer, Jürgen (European Journal of Organic Chemistry, 1998)
[4+2] Cycloadditions of thiobenzophenones 1a and thiofluorenones 2 with cyclic and open-chain dienes gave cycloadducts in high yields. Assignment of the product structure especially the regiochemistry of the cycloadditions involved H- and C-NMR spectroscopy, and single-crystal structure determination.